Expiratory effort exacerbates excessive dynamic airway collapse: a case report on esophageal pressure monitoring in a mechanically ventilated patient - Akira Kono; Chihiro Narita; Naoki Tosaka (The Egyptian Journal of Bronchology)
Abstract Background Excessive dynamic airway collapse (EDAC) has primarily been reported in patients with obstructive lung diseases, and its significance has recently gained increasing recognition in the field of intensive care. However, the diagnosis of EDAC requires a comprehensive approach, and it is particularly challenging in patients without underlying obstructive lung disease. Transpulmonary pressure (PL) is utilized in mechanical ventilation for the assessment of lung stress and strain, PEEP titration, and the evaluation of inspiratory effort. While numerous studies have reported on the use of PL to assess inspiratory effort, there are relatively few reports on its application in evaluating expiratory effort. Case presentation We report the case of a 64-year-old man with severe respiratory failure secondary to COVID-19. He was intubated due to respiratory acidosis and was diagnosed with acute exacerbation of COPD (AE-COPD) due to COVID-19. Despite mechanical ventilation, his condition worsened, necessitating VV-ECMO. For the management of AE-COPD, bronchodilators were administered, while pneumonia was treated with antibiotics and corticosteroids. Following hospitalization, expiratory time prolongation and lung compliance gradually improved; however, intermittent expiratory flow limitation persisted. Bronchoscopy revealed a prolapse of the membranous trachea without obstructive lesions, suggesting EDAC. Ventilator graphics demonstrated a significant increase in esophageal pressure (Pes) during expiration, indicating substantial expiratory effort, yet expiratory flow markedly decreased during this period. Based on these findings, we determined that expiratory effort exacerbated EDAC, leading to expiratory flow limitation; therefore, a tracheostomy was performed on the eighth day of hospitalization. On the ninth day, expiratory flow limitation improved, allowing for successful weaning from VV-ECMO. Tracheostomy decannulation was performed on the twenty-fifth day of hospitalization, and no recurrence of EDAC symptoms was observed thereafter. The patient was discharged on the thirty-eighth day. Conclusion In patients with EDAC, expiratory effort can exacerbate airway narrowing through the Bernoulli effect, leading to severe expiratory flow limitation. Conventional mechanical ventilation poses challenges in assessing expiratory effort; however, Pes measurement as a surrogate for pleural pressure allows its detection. In mechanically ventilated patients, Pes monitoring may facilitate the identification of EDAC exacerbation caused by excessive expiratory effort, aiding in diagnosis and management.